2021
DOI: 10.1177/08830738211028394
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acetyl-DL-Leucine on Ataxia and Downbeat-Nystagmus in Six Patients With Ataxia Telangiectasia

Abstract: Background: There is no authorized treatment for ataxia telangiectasia (AT). As cerebellar symptoms of storage diseases were improved by acetyl-DL-leucine (ADLL), the authors hypothesized a symptomatic and disease-modifying effect in AT upon supplementation with ADLL. Methods: Six patients were treated with ADLL 3 g/day for 1 week followed by 5g/day for 3 weeks to 1 year. Cerebellar ataxia was evaluated by validated scales. Gaze-holding, saccades and smooth pursuit were examined by video-oculography. Measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
0
1
0
2
Order By: Relevance
“…Eine andere Substanz zur Behandlung zerebellärer Ataxien ist die modifizierte essenzielle Aminosäure Acetyl-DL-Leucin. Hier wurden positive Effekte beschrieben im Tiermodell bei lysosomalen Speichererkrankungen [55,56] und in kontrollierten klinischen Studien bei Niemann-Pick Typ C [57] und Gangliosidose Typ 2 sowie in einer Anwendungsbeobachtung bei Patienten mit Ataxia telangiectasia [58]. Bei anderen Ataxien zeigte sich aber kein Effekt [59].…”
Section: Therapeutische Möglichkeiten Bei Ausgewählten Ursachen Eines...unclassified
“…Eine andere Substanz zur Behandlung zerebellärer Ataxien ist die modifizierte essenzielle Aminosäure Acetyl-DL-Leucin. Hier wurden positive Effekte beschrieben im Tiermodell bei lysosomalen Speichererkrankungen [55,56] und in kontrollierten klinischen Studien bei Niemann-Pick Typ C [57] und Gangliosidose Typ 2 sowie in einer Anwendungsbeobachtung bei Patienten mit Ataxia telangiectasia [58]. Bei anderen Ataxien zeigte sich aber kein Effekt [59].…”
Section: Therapeutische Möglichkeiten Bei Ausgewählten Ursachen Eines...unclassified
“…The effects of NADLL (dose of 3–5 g/day) in 6 patients with AT least over 4 weeks have been reported by Brueggemann et al in 2022. They showed that NADLL can improve ataxia and ocular stability in these patients [ 20 ]. Likewise, a recent case study suggested the beneficial effects of NADLL supplementation (4 g/day for 16 weeks) in improving ataxia and quality of life in a 9.7-year-old girl with AT [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eine andere Substanz zur Behandlung zerebellärer Ataxien ist die modifizierte essenzielle Aminosäure Acetyl-DL-Leucin. Hier wurden positive Effekte beschrieben im Tiermodell bei lysosoma-len Speichererkrankungen [55,56] und in kontrollierten klinischen Studien bei Niemann-Pick Typ C [57] und Gangliosidose Typ 2 sowie in einer Anwendungsbeobachtung bei Patienten mit Ataxia telangiectasia [58]. Bei anderen Ataxien zeigte sich aber kein Effekt [59].…”
Section: Therapeutische Möglichkeiten Bei Ausgewählten Ursachen Eines...unclassified